ENT530: As-Siraj Haj Umrah Travel & Tours Sdn Bhd / Muhammad Nazril Hakim Adenan, Nur Sazatul Anisa Sapuan and Siti Zubaidah Mohd Nor - Hakim Adenan, Muhammad Nazril; Sapuan, Nur Sazatul Anisa; Mohd Nor, Siti Zubaidah (2016)
As-Siraj Umrah Travel & Tours Sdn. Bhd. formerly known As Siraj which means a lamp, The meaning was given because a light that illuminated the umrah & hajj jemaah. It is a company that carries out the service of Umrah. In the beginning, Ahamed Musthafa bin Mohamed Hanifalim as a general manager handles this business in collaboration with the Maya Holiday Sdn. Bhd. In 2003, he registered his business in the name of Siraj Haj Umrah Services and established in operation with K.R.S Travel Sdn Bhd. On 2005, in order to expand its business, the company's name was converted to As-Siraj Haj Umrah Travel & Tours Sdn. Bhd. With this establishment, the company can handle business operations in a more organized and smooth. Throughout the company's business, the company has operated 8 Umrah packages through Maya Holiday Sdn Bhd and K.R.S Travel Sdn Bhd.